Methane and carbon fluxes measured at various locations within the drained thaw lake basin near Barrow, Alaska, 2012 ... - Miller, K.; Friedman, E.; Angenent, L.; Lipson, D.A. (NSF Arctic Data Center, 2013)
In 2012, gas fluxes were measured at various locations within the drained thaw lake basin previously used for the Biocomplexity Experiment (BE), near Barrow, Alaska (AK). In two separate experiments collars were arranged in three ice wedge polygons within the central region of the BE, referred to as A, B and C. Carbon dioxide-CO2 and methane-CH4 fluxes were measured using a Los Gatos Research portable trace gas analyzer. ...